KEANEKARAGAMAN JENIS GASTROPODA DI HUTAN MANGROVE DESA PADANG TIKAR I KECAMATANBATU AMPAR KABUPATEN KUBU RAYA - Darwati, Herlina; Andriani, Titi; Rifanjani, Slamet (JURNAL HUTAN LESTARI, 2023)
Gastropods as bioindicators of mangrove ecosystem stability. Information regarding Gastropods in the mangrove forest of Padang Tikar I Village and environmental changes are thought to influence the existence and abundance of Gastropod species. It is necessary to research the diversity of Gastropod species in the mangrove forests of Padang Tikar I Village, Batu Ampar District, Kubu Raya Regency. The research aims to calculate the diversity index of Gastropod species in the mangrove forest ecosystem in Padang Tikar I Village. The research uses a survey method, purposive sampling, and systematic data collection techniques, namely a combination of three grid lines. The identification results found 13 types of Gastropods from 7 families, namely Ellobiidae, Littorinidae, Muricidae, Neritidae, Nassariidae, Naticidae, and Potamididae. The gastropods that were often found were Nassarius stolatus on line one, Littorina scabra on line two, and Cerithidea cingulata on line three. The type with the greatest abundance is Cerithidea cingulata 45 ind/m2 dan Littorina scabra 14 ind/m2. Gastropod diversity in each route is in the low category. Some types dominate in line two, namely Littorina scabra and line three Cerithidea cingulata. The evenness of Gastropods in line one includes stable criteria, while lines two and three are unstable. The highest criteria type similarity is 57% in lines two and three, in lines one and two, and lines one and three 0%.Keywords: Abundance, Diversity, Gastropods, Mangrove.AbstrakGastropoda sebagai bioindikator kestabilan ekosistem mangrove. Informasi mengenai Gastropoda di hutan mangrove Desa Padang Tikar I dan perubahan lingkungan diduga mempengaruhi keberadaan dan kelimpahan jenis Gastropoda, perlu dilakukannya penelitian tentang keanekaragaman jenis Gastropoda di hutan mangrove Desa Padang Tikar I Kecamatan Batu Ampar Kabupaten Kubu Raya. Tujuan penelitian menghitung indeks keanekaragaman jenis Gastropoda pada ekosistem hutan mangrove di Desa Padang Tikar I. Penelitian menggunakan metode survei, teknik pengumpulan data secara purposive sampling dan sistematik yaitu metode kombinasi jalur garis berpetak sebanyak tiga jalur. Hasil identifikasi ditemukan 13 jenis Gastropoda dari 7 famili yaitu Ellobiidae, Littorinidae, Muricidae, Neritidae, Nassariidae, Naticidae, Potamididae. Gastropoda yang banyak dijumpai Nassarius stolatus pada jalur satu, Littorina scabra pada jalur dua, dan Cerithidea cingulata pada jalur tiga. Jenis dengan kelimpahan terbesar Cerithidea cingulata 45 ind/m2 dan Littorina scabra 14 ind/m2. Keanekaragaman Gastropoda pada tiap jalur termasuk kategori rendah. Terdapat jenis yang mendominasi pada jalur dua yaitu Littorina scabra dan jalur tiga Cerithidea cingulata. Kemerataan Gastropoda jalur satu termasuk kriteria stabil sedangkan jalur dua dan tiga labil. Kesamaan jenis kriteria tertinggi 57% jalur dua dan tiga, pada jalur satu dan dua serta jalur satu dan tiga 0%. Kata Kunci: Gastropoda, Keanekaragaman, Kelimpahan, Mangrove